Efficient α/β-Bi2O3 composite for the sequential photodegradation of two-dyes mixture. Issue 11 (15th August 2016) - Gadhi, Tanveer A.; Hernández-Gordillo, Agileo; Bizarro, Monserrat; Jagdale, Pravin; Tagliaferro, Alberto; Rodil, Sandra E.
Abstract: A mixture of α/β-Bi2 O3 and α-Bi2 O3 powders were obtained by a simple solid state reaction–annealing route at 550 °C. The structure, optical properties and surface area of the commercial α and β-Bi2 O3 and the synthesized α-phase and α/β-composite were well characterized by X-ray diffraction, diffuse reflectance spectra and N2 physisorption. The annealed sample at 550 °C showed 20% of β-phase, forming a heterojunction of α/β-Bi2 O3 whereas annealing at elevated temperature (650 °C) lead to the α-phase. Optical properties showed that the presence of the β-phase is mainly responsible for narrowing the energy band gap. The photocatalytic activity of the commercial α and β-Bi2 O3 and the synthesized α-phase and α/β-composite were investigated in degradation of single dyes, Indigo Carmine ( IC ) and Rhodamine-B ( RhB ) under both UV and visible light-induced photocatalysis. For the best photocatalyst, the photodegradation in a two-dye mixture solution was systematically studied considering the type of dye, the adsorption capacity of the samples and the behavior of dye photodegradation. The photocatalytic performance of α/β-Bi2 O3 was comparatively much higher than the commercial α and β-Bi2 O3, indicating that better performance of efficient charge separation and transfer across α/β-Bi2 O3 composite was obtained. Possible mechanism of the single dye and two-dye mixture degradation was given by using α/β-Bi2 O3 composite.